Meningkatkan Kemampuan Bahasa Ekspresif Anak Usia Dini Melalui Metode Bercerita dengan Media Gambar di PAUD Kober Zahrotul Hayat Kecamatan Ciracap - Alia, Pipi; Munajat, Asep; Zultiar, Indra (PT. Alahyan Publisher Sukabumi, 2024)
The background of this study is the expressive language skills of early childhood PAUD Kober Zahrotul Hayar including low so that it requires improvement. The purpose of this study was to determine the improvement of expressive language skills of early childhood PAUD Kober Zahrotul Hayar using the storytelling method with image media. The type of research used is Kemmis and Mc Taggart's design class action research. The research was conducted at PAUD Kober Zahrotul Hayar and group B children totaling 10 children became the research subjects. Data collection using observation, document study, and field notes then analyzed using descriptive statistical methods. Based on the results of observations it is known that in the pre-cycle, the percentage of pre-cycle ability the percentage of children's expressive language ability is 49.69% and is included in the criteria for starting to develop (MB). In cycle I there was an increase of 15.62% so the percentage of expressive language skills of early childhood was 65.31% and included in the criteria for development as expected (BSH). In cycle II there was an increase of 26.41% so in cycle II the percentage of expressive language skills in early childhood was 91.72% and included in the criteria for developing very well (BSB).